Microstructural and textural properties of rennet-induced milk protein gel: Effect of guar gum - Galante, Micaela (2018)
The knowledge of the effect of polysaccharide addition on the textural properties of milk protein gels is important for foodstuff engineering design. Therefore, the microstructure, texture, and water-holding capacity of rennet-induced milk protein gel with and without the addition of different concentrations of guar gum (GG) were determined. It was found that the presence of GG changed the microstructure of rennet-induced milk gel. The addition of a GG concentration higher than 0.075% w/v led to a discontinuous protein network. Changes in the structure of the gel samples are reflected in the texture perception and their capability of water retention. When a limit GG concentration of 0.15% w/v was exceeded, a very weak gel sample was obtained. The results demonstrated that different milk protein gel microstructures can be created by the addition of different concentrations of GG.